INTEGRATION OF INTERNAL AUDIT, ELECTRONIC AUDIT, AND AUDIT GOVERNANCE IN IMPROVING THE EFFECTIVENESS OF INTERNAL CONTROL AND REDUCING THE RISK OF FRAUD - Marsanda Ponelo; Mutiara Nandiva; Jasmine Nadia Podungge; Maimun Baode; Sahmin Noholo (PT. Jurnal Center Indonesia Publisher, 2026)
Digital transformation has increased the complexity of fraud risks within organizations, necessitating a more adaptive and integrated internal control system. This study aims to analyze the integration of internal audit, electronic audit, and audit governance in improving the effectiveness of internal control and mitigating fraud risks. This study uses a Systematic Literature Review (SLR) approach by analyzing various scientific literature relevant to the research topic. The results show that independent internal audit, the use of electronic audit technologies such as Big Data Analytics and Blockchain, and audit governance through Whistleblowing Systems and AI Governance have a synergistic relationship in strengthening organizational oversight systems. The integration of these three aspects can improve the effectiveness of fraud detection, maintain the integrity of audit data, and strengthen organizational transparency and accountability. This study provides a conceptual contribution in the form of a digital-based integrated oversight model as a strategy for strengthening internal control in the era of digital transformation.